Analysis of the Relationship of the Role of Father, Mother and Child in the Qur'an: Efforts to Realize a Sakinah Family Perspective of Analysis of Tafsir Al-Maraghi - Indah Artanti; Kiki Muhamad Hakiki; Beko Hendro (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2026)
This research is a study of interpretation that aims to analyze the relationship between the roles of father, mother, and child according to the perspective of the Qur'an based on Tafsir Al-Maraghi. The discussion focused on examining the roles of fathers, mothers, and children, including how the relationship of these roles in pursuing a sakinah family. The research method is qualitative which applies the content analysis method using a maudhu'i (thematic) approach and adopting the theory of the Family System from Salvador Minuchin. The search and selection of the study verse uses the word وَلِدِهِ - الولدت – الوَالِدَينِ and also uses the overall category of sentence meaning so that 15 sentences are collected. The results of this study show that fathers play a role in providing sustenance (Qs. al-Baqarah: 233, Qs. an-Nisa: 34), educating children (Qs. Luqman: 13-19, Qs. al-Baqarah: 233, Qs. an-Nisa: 9), and being leaders and mentors in the family (Qs. asy-Shu'ara, Qs. Maryam: 55, Qs. Taha: 132, Qs. an-Nisa: 34), then mothers play a role in breastfeeding children (Qs. al-Ahqaf: 15, Qs. al-Baqarah: 233) and educating children (Qs. al-Baqarah: 233, Qs. an-Nisa: 9), and that children have the role to do good and be devoted to their parents (Qs. al-Isra': 23, Qs. Luqman: 14-15, Qs. al-Ahqaf: 15), it was found that al-Maraghi also highlighted the importance of collaboration and good communication between fathers and mothers in caring for and caring for their children, then children are required to be devoted to their father and mother in all circumstances except for commands that lead to disobedience to Allah. The results of this research are expected to be an academic and practical reference for the development of Islamic family education.